Common Law Marriage and Male/Female Convergence in Labor Supply and Time Use - Shoshana Grossbard; Victoria Vernon (Institute for the Study of Labor (IZA), 2014)
Does availability of common law marriage (CLM henceforth) in the U.S help explain variation in the labor force participation, hours of work and hours of household production of men and women over time and across states? As CLM offers more legal protection to household producers at the margin between single status and marriage, we expect it to discourage labor supply and encourage household production on the part of household producers who are married or cohabit. In the context of traditional gender roles this implies a negative association between availability of CLM and the labor supply of women who are either married or cohabit. Also assuming traditional gender roles, men are then expected to work more in the labor force when CLM is available. We analyze micro data from CPS-iPums for the period 1995-2011 to investigate labor outcomes and from the ATUS for the period 2003-11 to study effects on household production and total hours of work. Labor supply effects of CLM availability are almost always negative for cohabiting and married women, and sometimes also for single women. The effects of CLM on men's labor supply tend to be negative when samples include all men aged 18-35. However, for the groups that we identified as most likely to be affected by CLM availability the youngest white men w/o college education we find positive effects. Married non-black men and women and work less in home production under CLM.
Keywords: J12; J16; J22; K36; 330; labor supply; marriage; law and economics; household production